Thickness effect on interdiffusion of Fe/Pt multilayers - Nguyen, Dan Phuong; Park, Chan-Woo; Lee, Young-Min; Shin, Keesam; Choi, Hee-Kyu; Chung, Woo-Hyun; Lee, Chan-Gyu (Metals and materials international, 2008)
The effect of thickness on interdiffusion in Fe/Pt multilayer thin films was studied using rapid thermal annealing. [Fe(1 nm)/Pt(1 nm)] 20 and [Fe(3 nm)/Pt(3 nm)] 10 multilayers were prepared via DC magnetron sputtering and subsequently annealed at temperatures of 523 K to 603 K in an argon atmosphere in an infrared lamp furnace for a very short time. X-ray diffraction yielded the interdiffusion coefficients from the slopes of the satellite peak versus annealing time. The temperature dependence of interdiffusion in the range of 523 K to 603 K can be described by D(t) =3.42×10 −15 exp(−0.83 eV/k B T) (m 2 /s) for [Fe(1 nm)/Pt(1 nm)] 20 and D(t) =7.85×10 −16 exp(−0.62 eV/k B T) (m 2 /s) for [Fe(3 nm)/Pt(3 nm)] 10 . The activation energy Q=0.83 eV for [Fe(1 nm)/Pt(1 nm)] 20 is higher than that of Q=0.62 eV for [Fe(3 nm)/Pt(3 nm)] 10 . This phenomenon suggests that the atoms in the thicker film can move more easily in the interface and the lattice, which results in lower activation energy and higher diffusivity.